Multiobjective-Optimized Design of a New UWB Antenna for UWB Applications - C. Moreno de Jong van Coevorden; M. Fernández Pantoja; Salvador G. García; A. Rubio Bretones; R. Gómez-Martín; K. Palmer (International Journal of Antennas and Propagation)
A multiobjective genetic algorithm has been applied to design a new printed, bow-tie antenna for ultrawideband applications, that is, ground penetrating radar, short range and high data rate communications, and so forth. The ultrawideband performance with respect to antenna impedance and gain is achieved by an optimized resistive loading profile and flare angle. A low-cost prototype is manufactured and numerical simulations are validated with measurements.